Conflict Management in Organizations - Sucharitkul, Juthathip (Rajapark Journal, 2022)
This article was primarily concerned with the conflict management within an organization to analyze and synthesize the causes and the conflict management via relevant meanings and concepts of conflict management based on a systematic review of literature which was considered a research instrument for a content analysis of the case study of the conflict management. The concepts and suggestions including conceptual framework, concepts of conflicts, causes of conflicts, types of conflicts, and the conflict management in the organization were inductively presented. It was found that conflicts within an organization were inevitable conditions. Six types of conflict within the organization included 1) Interpersonal Conflict, 2) Interpersonal Conflict, 3) Intergroup Conflict, 4) Intergroup Conflict, 5) Intra-organization Conflict, and 6) Inter-organizational Conflict. Additionally, five methods of conflict management within the organization included 1) Competition or Subjugation, 2) Cooperation, 3) Avoidance, 4) Acceptance, and 5) Compromise. A key to successful and constructive conflict management was a must for the organization leader to realize the nature of conflict, acknowledge the opinions of employees, and employee’s participation within the organization to be a starting point of conflict management in organizations.